The Performance Assessment of Irrigation System on Tertiary Irrigation Network of Jabung Irrigation Area, East Lampung Regency: Performance Assessment of Irrigation System on Tertiary Irrigation Network of Jabung Irrigation Area, East Lampung Regency - Mahardika, Siti; Dyah Indriana Kusumastuti; Endro Prasetyo Wahono; Nur Arifaini (Universitas Negeri Surabaya, 2025)
Jabung Irrigation Area is one of the irrigation areas located in East Lampung Regency with an area of 7,288 hectares. Jabung Irrigation Area has a problem of uneven water distribution. This problem occurs in the downstream area due to damage to physical infrastructure, especially in tertiary irrigation canals, and sub-optimal operation and maintenance activities. Therefore, based on the Minister of Public Works and Housing Regulation No. 12/PRT/M/2015 concerning the Exploitation and Maintenance of Irrigation Networks, a study was conducted on determining the Irrigation System Performance Index (IKSI) of the tertiary network in the Jabung Irrigation Area. The purpose of this study is to assess the performance of the tertiary irrigation system of the Jabung Irrigation Area which is useful for formulating follow-up programs such as repair, rehabilitation, and maintenance of the irrigation network. The research method was carried out using a qualitative descriptive method and direct assessment in the field as well as interviews. The assessment covers 6 aspects, namely the condition of physical infrastructure, crop productivity, supporting facilities, personnel organization, documentation, and Farmers' Water Users Association (P3A). The results showed that the performance of the tertiary irrigation network in the Jabung Irrigation Area is in good condition (70.54%).